U-shaped association between dietary niacin intake and chronic kidney disease among US elderly: a nationwide cross-sectional study - Xie, Zhouzhou; Peng, Shansen; Ou, Gejun; Zhou, Xiaoqi; Zhang, Guihao; Jiang, Huiming; Zhang, Tianhui; Chen, Nanhui (Frontiers in Endocrinology, 2024)
Background: In addition to hypertension or diabetes, elderly people are also considered one of the high-risk groups for chronic kidney disease (CKD). Although niacin is recognized for its renal protective properties, the link between dietary niacin intake and CKD remains uncertain. This study investigated this relationship in the elderly.Methods: We included participants aged 60 and older from the National Health and Nutrition Examination Survey (NHANES) for the years 2003-2018. Dietary niacin intake was assessed through two non-consecutive 24-hour dietary recalls. CKD was diagnosed in individuals with a urine albumin-to-creatinine ratio exceeding 30 mg/g or an estimated glomerular filtration rate below 60 mL/min per 1.73 m^2. The study cohort comprised 4,649 participants, 1,632 of whom had CKD. Propensity score matching (PSM) was utilized to adjust for baseline differences between the groups.Results: Our analysis, using smooth curve fitting and generalized additive models both before and after PSM, found a U-shaped curve depicting the relationship between dietary niacin intake and CKD risk, confirmed by a log-likelihood ratio test (P < 0.05). Threshold effect analysis (after PSM) indicated a reduced risk of CKD in older adults with a niacin intake below 38.83 mg per day [odds ratio (OR) = 0.99, 95% confidence interval (CI) 0.97-1.00]. In contrast, higher intake levels significantly increased the risk (OR = 1.03, 95% CI 1.00-1.06). Subgroup analysis indicated that these associations were consistent across different stratification variables (P for interaction > 0.05).Our findings suggested a U-shaped association between dietary niacin intake and CKD risk among older Americans. However, further prospective cohort studies are needed to confirm this finding.